Maximal and submaximal exercise performance at altitude - Fulco, C. S.; Rock, P. B.; Cymerman, A. (Aviation, Space, and Environmental Medicine, 1998)
BACKGROUND: Exercise performance data of numerous altitude research studies and competitive sporting events of the last four decades are reviewed. METHODS: The primary focus is on the wide interindividual variation associated with maximal and submaximal exercise performance that occurs at different altitudes and for different periods of time at altitude. RESULTS: Fitness level, pre-exposure resident altitude, gender, and duration of altitude exposure are qualitatively assessed to determine their contribution to the overall variability. Of these, pre-altitude exposure fitness level difference contributes the most variability and gender difference contributes the least. It is also determined that beginning at an altitude of 580 m, maximal aerobic power (VO2max reduced and does not improve with extended exposure as long as the individual's level of fitness level is not altered significantly by increases in activity, exercise training or by altitude-induced physical deterioration. Submaximal exercise performance is also impaired at altitude. CONCLUSION: By assessing the performance of elite athletes, who are performing at an "all-out" effort in precisely timed events for which they are trained, it is determined that: a) the magnitude of submaximal exercise impairment is proportional to both the elevation and exercise duration at a given altitude; and b) submaximal exercise performance at altitude can improve with continued exposure without an increase in VO2max. Muscle strength, maximal muscle power, and anaerobic performance at altitude are not affected as long as muscle mass is maintained. In addition, performance is not impaired in athletic activities that have a minimal aerobic component and can be performed at high velocity (e.g., sprints).